Early Childhood Education in Islamic Perspective - Ramli, Muhammad Amirul (Bulletin of Early Childhood, 2022)
The teachings of Islam, the Qur'an has given guidance about how to prepare generation or a child as a trustee, to make him a human being who can carry out of Islamic law well. The article disscused of the educational process and the developmental needs of early childhood in islamic perspective. The researchers used a qualitative method by reviewing some of the previous findings with a coding system and in-depth analysis of each data. The collecting data used documentation, from online publication research. The researchers collected the data on online search publications, for instance Google Scholar, Science Direct, et all, specifically on articles published between 2010 and 2021. The result showed that several methods of Islamic education that be applied to educational activities for early childhood, for instance method by example, education by practice and practice, educating through games, songs, and stories, educating with targhib and tarhib, praise and flattery, instilling good habits.